Genome-Wide Identification of Host Genes Required for Toxicity of Bacterial Cytolethal Distending Toxin in a Yeast Model - Denmongkholchai, Siriyod; Katare, Prashant; Choochuay, Sarocha; Thanyasrisung, Panida; Tsuruda, Keiko; Sugai, Motoyuki; Mongkolsuk, Skorn; Matangkasombut, Oranart (Frontiers in Microbiology, 2019)
Background: Aggregatibacter actinomycetemcomitans, a periodontal pathogen, secretes a cytolethal distending toxin (AaCDT) that causes host cell cycle arrest and cell death. Although CDT could be an important virulence factor, how it enters the nucleus to exert its cytotoxicity is unclear. Objective: To investigate the mechanisms of AaCDT by genome-wide screening for host mutations that confer resistance to the catalytic subunit, AaCdtB, in a Saccharomyces cerevisiae model. Methods: We transformed the yeast haploid deletion library, a collection of yeast mutants with single gene deletions of virtually all non-essential ORFs in the genome, with plasmids carrying galactose-inducible AaCdtB. Yeast mutants that showed resistance to AaCdtB were selected and rescreened by spotting assay. AaCdtB expression was confirmed by western blot analysis; any mutants that showed no or weak expression of AaCdtB were omitted from the analysis. The lists of genes whose mutations confer resistance to AaCdtB were analyzed for Gene Ontology (GO) term enrichments. Localization of AaCdtB-EGFP was examined using fluorescent microscopy. Nuclear localization relative to EGFP control was calculated and compared to wild-type. Results: From approximately 5,000 deletion mutants, we isolated 243 mutants that are resistant to AaCdtB. GO analyses indicated that genes associated with organic anion transport is significantly enriched (16 genes). Furthermore, several genes associated with nucleus and endoplasmic reticulum (ER) were identified. Localization studies of AaCdtB in mutants with the deletion of genes associated with the GO term organic anion transport showed lower nuclear localization than wild-type. The results suggest that these genes may be required for AaCdtB translocation into the nucleus and its cytotoxicity. Conclusions: The genome-wide screen in the yeast deletion library allowed us to identify a large number of host genes required for AaCdtB cytotoxicity. Further investigation could lead to more insights into the mechanisms of CdtB intoxication.